Analisis Indeks Kepuasan Masyarakat Terhadap Pelayanan Publik Pada Perumda Air Minum Tirta Baribis Kabupaten Brebes Berdasarkan Indeks Kepuasan Masyarakat - Rani Reviyana Purwanti; Muhammad Syaifulloh; Slamet Bambang Riono (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research has the main objective, namely to determine the service at the Tirta Baribis Drinking Water Company, Brebes Regency, which is measured based on the community satisfaction index which refers to the guidelines of the Ministerial Regulation on State Apparatus Empowerment and Bureaucratic Reform of the Republic of Indonesia Number 14 of 2017. The sampling technique used is non-probability. sampling with the type of accidental sampling. Data collection techniques were carried out using observation, documentation and distributing questionnaires to 177 respondents. The validity test uses the Pearson Product Moment formula and the reliability test uses the Cronbach's Alpha formula. The results of calculating the Community Satisfaction Index in this study were evaluated based on 9 elements, showing that services at Perumda Air Minum Tirta Baribis received a score of 2.98 with a conversion rate of 74.55, this value shows that 74.5% of the community felt satisfaction with the services provided, so that public services at the Tirta Baribis Drinking Water Company are at service quality level